Towards an Interdisciplinary Focus on Sound in Ethnobiology Research - Wright, Claire C (Ethnobiology Letters, 2017)
Research on perception and ecological knowledge in ethnobiology has primarily focused on sight, in tandem with taste, smell, and touch. Sound, however, has been largely neglected as a topical or methodological focus. This review addresses research in ethnomusicology and soundscape ecology to suggest how attention to sound could open new avenues and add value to ethnoecological research.